KETIDAKFASIHAN BERBICARA PARA PEMERAN DALAM SERIAL FILM HARRY POTTER ENAM DAN TUJUH (SUATU ANALISIS PSIKOLINGUISTIK) - OROH, PRISKY ROOSLINE DEBORA (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2016)
ABSTRACT This study which is entitled â€œKetidakfasihan Berbicara Para Pemeran dalam Serial Film Harry Potter Enam dan Tujuh (Suatu Analisis Psikolinguistik)â€ is an attempt to identify the types of speech disfluencies of the characters in the serial films Harry Potter Six and Seven and to analyze the causes of those speech disfluencies. In classifying and analyzing the collected data, the writer uses Fox-Three (1995) and MacGregorâ€™s (2008) theory about the types of speech disfluencies, and Bortfeldâ€™s et al. (2001) theory of what cause the speech disfluencies. It is found that five types of speech disfluencies are produced by the characters in the Serial Films Harry Potter Six and Seven. That types are, silent pause, filled pause, repetition, repair, and lexical filler. Repetitions is the types of disfluencies are the most founded because of the increaseÂ  in cognitive process that results to a heavy planning in utterances. The causes of speech disfluencies of the characters in serial films Harry Potter Six and Seven are by variables such as, cognitive load, communication medium, topic under discussion, addressee characteristic, speaker characteristic, as well as social and situational factors. It is because we encounter those variables in almost every time. Age is not found to cause of speech disfluencies in the serial films Harry Potter because as there arenâ€™t many older people characters in the serial films. This study will help students and the next researchers in expanding their knowledge about speech disfluencies and language production. Â  Keywords: Speech Disfluencies, Harry Potter Films, Psycholinguistic Analysis